2003
DOI: 10.1111/j.0022-3506.2004.00258.x
|View full text |Cite
|
Sign up to set email alerts
|

Borderline Personality Features and Instability of Daily Negative Affect and Self‐Esteem

Abstract: We used a daily process design and multilevel modeling to examine the role of borderline personality features in the day-to-day stability of college students' negative affect and self-esteem and their reactivity to interpersonal stressors. At the end of each day for two weeks, students completed a checklist of daily stressors and measures of state affect and self-esteem. We predicted that high scores on a measure of borderline features would be related to more daily interpersonal stressors, greater negative af… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 56 publications
(13 citation statements)
references
References 41 publications
0
12
0
Order By: Relevance
“…This may be explained by BPD patients’ characteristic oscillations of emotion, identity, and self- and other-evaluations (Tolpin et al, 2004; Lynum et al, 2008). Additionally, the IAT itself shows moderate test–retest reliability, with an average r  = 0.56 across nine studies (Nosek et al, 2007).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This may be explained by BPD patients’ characteristic oscillations of emotion, identity, and self- and other-evaluations (Tolpin et al, 2004; Lynum et al, 2008). Additionally, the IAT itself shows moderate test–retest reliability, with an average r  = 0.56 across nine studies (Nosek et al, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have found a correlation between BPD features (BPDF) and labile, low self-esteem (Watson, 1998; Tolpin et al, 2004; Zeigler-Hill and Abraham, 2006). Further, Lynum et al (2008) found that participants with BPD had higher explicit self-esteem as reported on the Self-Esteem Index than those with avoidant personality disorder (APD), although both groups scored in the clinical range of low self-esteem.…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, self-descriptions and attitudes towards themselves are at least somehow unstable in those with BPD [ 92 , 107 , 123 , 124 ]. This is in line with the experience of a poor sense of self, which constitutes a diagnostic criterion of BPD [ 92 ].…”
Section: Self-referencementioning
confidence: 99%
“…In a population-based sample of married adults (n = 1,127; 635 females), BPD symptom severity was positively associated with marital distress, perpetration of minor and severe marital violence, and marital disruption even after controlling for the presence of 12-month axis I disorders [112]. Similarly, individuals with high levels of BPD traits experienced more negative daily interpersonal events than individuals with low levels of BPD traits [113,114]. …”
Section: Impaired Intimacymentioning
confidence: 99%